Association between maternal reflective function and preschool children’s cognitive abilities - Komanchuk, Jelena; Dewey, Deborah; Giesbrecht, Gerald F.; Hart, Martha; Anis, Lubna; Ntanda, Henry; Cameron, Judy L.; Letourneau, Nicole (Frontiers in Psychology, 2022)
Children’s cognitive abilities (e.g., working memory) are associated with mental health, adaptive behaviors, and academic achievement, and may be enhanced by parental reflective function (i.e., capacity to reflect on mental states, feelings, thoughts, and intentions in one’s child and oneself). We evaluated associations between maternal reflective function and children’s cognitive abilities alone and while controlling for parent-child attachment and interaction quality, and psychosocial (i.e., maternal depressive symptoms, adverse childhood experiences) and sociodemographic (e.g., socioeconomic status) factors. Our sample, recruited in Canada, was primarily white and included 73 mothers and their four- to five-year old preschool children. Maternal reflective function was measured with the Reflective Functioning Scale applied to the Parent Development Interview and the Parental Reflective Functioning Questionnaire. Multiple regression analyses revealed that maternal reflective function was associated with children’s cognitive abilities. The Parent Development Interview rated child-reflective function was associated with children’s higher verbal comprehension alone and while adjusting for covariates (e.g., parent-child interaction quality, socioeconomic status), and the Parental Reflective Functioning Questionnaire Interest and Curiosity with higher verbal comprehension while adjusting for parent-child interactions and attachment pattern. The Parental Reflective Functioning Questionnaire Certainty in Mental States was associated with higher working memory scores for children while adjusting for covariates. Full Scale IQ and Visual Spatial Index were not significantly associated with maternal reflective function. Associations were found between secure and disorganized attachment with higher verbal comprehension and lower working memory, respectively. These findings highlight the importance of high maternal reflective function to cognitive abilities in early childhood.